A Critical Evaluation of CALL and MALL Products for Learning and Teaching American English - İbrahim Halil Topal (e-Kafkas Eğitim Araştırmaları Dergisi)
Research conducted in diverse contexts revealed a general tendency among language learners and teachers toward mainstream English varieties. There is even a scientific foundation for this personal preference, suggesting that these varieties (particularly American English) are understood better. Besides, computer- and mobile-assisted technologies have fostered language education in general and the learning and teaching of these varieties. Accordingly, this study evaluated the CALL and MALL products (i.e., three websites, one mobile application, and one corpus) about American English using the adapted frameworks of Baya’a et al. (2009) and Reinders and Pegrum (2017). With a particular focus on the technical and pedagogical features and concerns, the analyses indicated potential advantages to language learners and teachers in grammar, pronunciation, vocabulary, listening, reading, intercultural awareness/competence, and pragmatic awareness at varying degrees. The evaluated products’ shortcomings (e.g., insufficient assessment and feedback) were also cited. The study revealed its limitations and made recommendations for further research. It further bridged the gap in the related literature and contributed to our understanding by providing insights.